If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 86 + -2x = 6 + -10x Solving 86 + -2x = 6 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 86 + -2x + 10x = 6 + -10x + 10x Combine like terms: -2x + 10x = 8x 86 + 8x = 6 + -10x + 10x Combine like terms: -10x + 10x = 0 86 + 8x = 6 + 0 86 + 8x = 6 Add '-86' to each side of the equation. 86 + -86 + 8x = 6 + -86 Combine like terms: 86 + -86 = 0 0 + 8x = 6 + -86 8x = 6 + -86 Combine like terms: 6 + -86 = -80 8x = -80 Divide each side by '8'. x = -10 Simplifying x = -10
| 1/x^3=0 | | 0=x-4+3x | | 1/x^3 | | 2xy+3z+1=0 | | x-3-8x-6= | | 5x-2=13x-19 | | 5w^2-30w+40=0 | | 80-5x+4x+10+80=180 | | -6(4y)= | | 6u+6(u-6)=36 | | 4x+10+80-5x=180 | | 13d^2-7d=0 | | -x+17y=127 | | 4(2x-1)-(-3+7)= | | 2y+9=4y-3 | | -1-7x=36x+6(-7-x) | | 4x^4y-36x^3y+80x^2y= | | (17+a)+12= | | x+3=x+11 | | 3z=6z-1 | | 2(-1-3x)=25+3x | | 4M-2(M+6)=5(3M-2)+6 | | 4+4(4x-4)=8-3(2x+1) | | 2y+2=-3 | | 5a-2+3a=17+12a-23 | | x^2-8x+64= | | Y=4Y^2-32Y+65 | | 7(w-8)+7w=14 | | 2x+10+4x-20=180 | | 2t+2=11 | | 5Q-3+2Q=10+9Q-3 | | 3x-10+2x+10=180 |